2015
DOI: 10.4314/jab.v91i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Change in a ferralsol physico-chemical properties under pineapple cropping system in southern of Benin

Abstract: Objectives:The study examines the evolution of soil properties under the main pineapple cropping system, in order to evaluate the effectiveness of this system towards maintaining sustainable productivity. Methodology and Results: The plots of different cropping durations (1.5, 3, 6, 7, 10, 15 and 16 years) were selected from the predominant pineapple cropping system. A fallow plot was identified in a neighbourhood of each selected pineapple plot. Soil profiles were installed in the selected fields and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…This also reflects the failure of their production techniques to maintain productivity, despite the use of mineral fertilizers. However, Sossa et al (2015) showed that these cropping systems affect the physical quality of the soil after 10 years and the chemical quality after 7 years of continuous use. For this shifting cultivation system, the abandonment of cultivated fields is not only due to soil fertility decline, but pathogens also harbored in the soil (Rohrbach and Johnson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This also reflects the failure of their production techniques to maintain productivity, despite the use of mineral fertilizers. However, Sossa et al (2015) showed that these cropping systems affect the physical quality of the soil after 10 years and the chemical quality after 7 years of continuous use. For this shifting cultivation system, the abandonment of cultivated fields is not only due to soil fertility decline, but pathogens also harbored in the soil (Rohrbach and Johnson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In this area, average annual rainfall is 1200 mm. The dominant soil type is a low-desaturated lateritic soil, commonly called "terre de barre" [22]. The soil physico-chemical analysis indicates that this is a soil of silty-clay-sandy texture, well drained, with an average pH of 5.6 and a C/N ratio of 11.2.…”
Section: Study Areamentioning
confidence: 99%
“…Malgré tous ses atouts, la production de l'ananas est limitée par la dégradation rapide de la fertilité des sols (Sossa et al, 2015 ;Atchada et al, 2021) ; ceci pourrait s'expliquer par une diversité des pratiques culturales (Agbangba et al, 2008 ;Agbangba et al, 2010). En effet, Sossa et al (2014) ont identifié cinq différents systèmes de culture d'ananas au Bénin qui se distinguent entre autres par les quantités d'engrais minéraux utilisées.…”
Section: Introductionunclassified